Reply to “‘Oh This Division of Allegiance!’ Being Both Irish and British?” - Harte, Liam (ABEI Journal, 2013)
The author responds to Elizabeth Malcolm ‘s critique to the book The Literature of the Irish in Britain: Autobiography and Memoir, 1725-2001.Harte reflects upon the process of making an anthology and points out thechallenging aspects of his research considering the constitutive complexity of autobiographical works when they are taken as historical sources.Keywords: the Irish in Britain; autobiography; memoir